Retaining Generation Y executives within Gabonese companies : the importance of the anchor-career success duo - (:unkn) unknown (My University, 2020)
ABSTRACTMany predictions (Tulgan and Martin, 2001; Guerfel-Henda, 2010; Gendron, 2011; Boutelet et al., 2011; Fabiet al., 2011) suggest that Generation Y is expected to play a crucial role in organizations. It should particularly fill the gap left by the Baby boomers retiring (Giraud, 2012; Delaye, 2013). However, the flattening of organizational structures, as a result of the digitalization of activities within companies, significantly reduces the opportunities for progress among young people who feel they are capping earlier than expected. Consequently, frustrated and dissatisfied with the progression ladders, they are ready to leave their companies at the slightest opportunity. This phenomenon, recognized by both professional and academic literature, is characterized among them by opportunistic behavior, weak institutional loyalty and difficulty in projecting themselves into the long term. Its resolution emerges as a major challenge for organizations, since there is every reason to believe that the most successful company will be the one that would have built and retained a pool of young managers (Fabi, Lacoursière, Morin and Raymond, 2010; Kleber and Persson, 2016).In addition, the African continent has the first reservoir of people belonging to Generation Y (200 million) according to the latest World Bank report (2014). In its new report “ World Employment and Social Outlook: Trend 2020”, the ILO predicts that the number of young people between the ages of fifteen (15) and twenty-four (24) is expected to reach two hundred and eighty-three (283,000,000) million by 2030 in Sub-Saharan Africa alone. Yet research on this topic is scarce and current knowledge on the organizational allegiance of young managers in Africa is insufficient (Kamdem and Tidjani, 2010; Mutabazi, 2006). The need to study different types of populations is acute in order to respond effectively to organizational career dynamics in the African context (Kamdem, 2002; Dany et al
Keywords: African Research